Inhibition of monoamine oxidase by indole-5, 6-dicarbonitrile derivatives. Issue 6 (15th March 2015) - Chirkova, Zhanna V.; Kabanova, Mariya V.; Filimonov, Sergey I.; Abramov, Igor G.; Petzer, Anél; Petzer, Jacobus P.; Firgang, Sergey I.; Suponitsky, Kyrill Yu.
Graphical abstract